2018
DOI: 10.1111/hdi.12659
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in kidney transplantation‐changing paradigms with novel agents

Abstract: Hepatitis C virus (HCV) is a common cause of increased morbidity and mortality in kidney transplant patients. It is associated with posttransplant glomerulonephritis, chronic allograft nephropathy, and New Onset Diabetes after Transplant (NODAT). In the past, HCV was difficult to treat due to the presence of interferon alpha-based therapies that were difficult to tolerate and were associated with adverse side-effects, such as the risk of rejection. With the advent of oral directly acting antiviral therapies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(202 reference statements)
0
4
0
Order By: Relevance
“…In the context of high SVR rates across all studied CKD populations, strategies about the timing of treatment in CKD are of paramount importance . For instance, HCV‐infected kidney transplant candidates who are willing to accept the kidney from an HCV‐infected donor can lose their advantage of an often dramatically shorter wait‐list time if they choose to be treated pretransplantation (and, thus, no longer be eligible for an HCV‐infected kidney) . Conversely, delaying treatment until after transplantation increases the risk of posttransplant diabetes mellitus and HCV‐associated glomerulonephritis (GN) .…”
Section: Kdigo Guideline Recommendationsmentioning
confidence: 99%
“…In the context of high SVR rates across all studied CKD populations, strategies about the timing of treatment in CKD are of paramount importance . For instance, HCV‐infected kidney transplant candidates who are willing to accept the kidney from an HCV‐infected donor can lose their advantage of an often dramatically shorter wait‐list time if they choose to be treated pretransplantation (and, thus, no longer be eligible for an HCV‐infected kidney) . Conversely, delaying treatment until after transplantation increases the risk of posttransplant diabetes mellitus and HCV‐associated glomerulonephritis (GN) .…”
Section: Kdigo Guideline Recommendationsmentioning
confidence: 99%
“…HCV infection prevalence in the hemodialysis (HD) population ranges from appropriately 3.6 to 15% in different countries [7,8]. Additionally, HCVassociated liver disease increases the risk of graft rejection, infection, and diabetes in patients receiving a kidney transplant [9][10][11], which indicated that eradication of HCV infection before transplantation would guarantee the transplantation success.…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of HCV in patients with end‐stage renal disease awaiting kidney transplant (KT) ranges from 1.4% to 2.1%, and the prevalence is estimated between 12% and 23% . HCV infection is associated with many adverse outcomes post‐KT, including an increased risk of acute rejection, chronic allograft nephropathy, diabetes and de novo glomerulonephritis …”
Section: Introductionmentioning
confidence: 99%
“…1 HCV infection is associated with many adverse outcomes post-KT, including an increased risk of acute rejection, chronic allograft nephropathy, diabetes and de novo glomerulonephritis. 2,3 Over the past several years, there has been a surge in HCV positive organs that are potentially available to the donor pool due to the growing opioid epidemic in the United States. In the last 5 years, the number of high-risk organ donors has increased and it is estimated that they make up 25% of the deceased donor pool.…”
mentioning
confidence: 99%